Distribution Characteristics Based on Data Analysis of Edible Vegetable Oil Supermarkets in SY City. Issue 4 (April 2021) - Wang, Yujie; Wu, Yaoting; Fu, Licheng; Wang, Rui; Feng, Suping
Abstract: Market research on edible vegetable oils of six main supermarkets in SY City and distribution characteristics based on data analysis including brands, types, packages, and prices of edible vegetable oils were studied, in order to understand the market characteristics of edible vegetable oils and judge the market trend of edible vegetable oils. Results show that edible vegetable oil market of six main supermarkets in SY is oriented by soybean oil, colza oil, peanut oil and blend oil, among which peanut oil and blend oil are dominant with equal occupancy of 21.3% and total occupancy of 41.6%. Tea oil, olive oil, flaxseed oil and other small-variety vegetable oils have also occupied certain market shares gradually. A total of 29 brands are investigated and four brands including JLY, LH, FLM and CSH occupy 51.8%. Edible vegetable oils are packaged in sizes 0.25L to 5L and two popular packing specifications are 1.8L and 5L. 1.8L packing specification occupies 59.6%. Vegetable oil prices investigated from RMB10 to RMB30 per litre occupy 78.0%.